Inhibitory Test of Onion Extract (Allium Cepa L.) Against The Growth of Trichophyton rubrum Fungus Causing Tinea Pedis - Heru Laksono; Ahmad Ade Saputra; Sunita Raden; Jon Farizal; Dahrizal Dahrizal (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Tinea pedis is a disease that attacks the area between the fingers, soles of the feet, heels, nails and is a source of infection in other areas. Trichophyton rubrum is the cause of 70 % of cases of tinea pedis. Fungal infections are usually treated using antifungal drugs which mostly have limitations, such as poor penetration into certain tissues, narrow spectrum of fungi, high side effects, and resistance of fungi to certain antifungals. Utilization of natural materials is done as an alternative treatment for fungal infections. One of the natural ingredients that has the potential to be used as antifungal is onion (Allium cepa L.). The aim of the study was to determine the ability of onion extract to inhibit the growth of the fungus Trichophyton rubrum. The type of research is Experimental Laboratory. This study used onion extract concentrations of 70 %, 60 %, 50 %, 40 %, control (+) and control (-). Data analysis using Kruskal Wallis Test and Post Hoc Mann Whitney Test. The average diameter of the inhibition zone at the extract concentration of 70 %, 60 %, 50 %, and 40 %, respectively, was 2,01 mm, 1,75 mm, 0,87 mm, and 0.58 mm. The results of the in vitro test using the disc diffusion method showed that onion extract had the ability to inhibit the growth of Trichophyton rubrum with a weak category.